Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41598-018-34507-3
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic approach for understanding milder neurotoxicity of Carfilzomib against Bortezomib

Abstract: The proteasomal system is responsible for the turnover of damaged proteins. Because of its important functions in oncogenesis, inhibiting the proteasomal system is a promising therapeutic approach for cancer treatment. Bortezomib (BTZ) is the first proteasome inhibitor approved by FDA for clinical applications. However neuropathic side effects are dose limiting for BTZ as many other chemotherapeutic agents. Therefore second-generation proteasome inhibitors have been developed including carfilzomib (CFZ). Aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…Recent studies have shown that bortezomib causes acute cytoskeletal damage, which is relevant in neural cell integrity. In addition, it has been demonstrated that bortezomib causes excessive protein carbonylation and destabilization of actin filaments [17]. Our current study provided interesting results that indicate a significant dysregulation of genes in neuronal cells, which may be characteristic for bortezomib activity (Figures 2, 3 and 8).…”
Section: Discussionsupporting
confidence: 59%
“…Recent studies have shown that bortezomib causes acute cytoskeletal damage, which is relevant in neural cell integrity. In addition, it has been demonstrated that bortezomib causes excessive protein carbonylation and destabilization of actin filaments [17]. Our current study provided interesting results that indicate a significant dysregulation of genes in neuronal cells, which may be characteristic for bortezomib activity (Figures 2, 3 and 8).…”
Section: Discussionsupporting
confidence: 59%
“…Under current-clamp potential recordings, the addition of CFZ was found to depolarize the cells, to widen AP duration, and to raise the firing frequency of spontaneous APs recorded from GH 3 cells in a concentration-dependent fashion. It is thus most likely that CFZ-induced increase of I K(DR) inactivation in endocrine or neuroendocrine cells may enhance a process of long-lasting facilitation or potentiation (Lin et al, 2008; Wang et al, 2008b; Wu et al, 2008; Kuo et al, 2018), which is conceivably associated with the toxicological actions of CFZ and other structurally similar compounds including variable forms of peripheral neuropathy (Cai et al, 2016; Kaplan et al, 2017; Karademir et al, 2018; Luczkowska et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Predominantly through the inhibition of proteasome-mediated proteolysis, the presence of CFZ can induce cell cycle arrest and apoptosis in different types of human cancer cell lines including multiple myeloma, lymphoma, and various solid tumors (Demo et al, 2007; Zhang and Sidhu, 2014; Kaplan et al, 2017). Moreover, there were case reports on CFZ associated neurotoxicity (Kaplan et al, 2017; Karademir et al, 2018; Luczkowska et al, 2018). However, how this agent and other structurally similar compounds exert any perturbations on membrane ionic currents is not thoroughly investigated, although CFZ might manipulate the energy and redox metabolism through a mechanism independent of its inhibition of proteasome activity (Soriano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The altered microtubule dynamics result in decreased neurite elongation and impaired axonal transport of mitochondria in mice and rat DRG neuronal cultures, respectively [90,91]. In addition, bortezomib can affect another major component of the cytoskeleton, the actin filaments, as observed in mouse neural stem cells [92].…”
Section: Peripheral Neuropathy: the Key Dose-limiting Toxicitymentioning
confidence: 99%